Bilateral lesions in a specific subregion of posterior insular cortex impair conditioned taste aversion expression in rats. Issue 1 (29th July 2015) - Schier, Lindsey A.; Blonde, Ginger D.; Spector, Alan C.
Abstract: The gustatory cortex (GC) is widely regarded for its integral role in the acquisition and retention of conditioned taste aversions (CTAs) in rodents, but large lesions in this area do not always result in CTA impairment. Recently, using a new lesion mapping system, we found that severe CTA expression deficits were associated with damage to a critical zone that included the posterior half of GC in addition to the insular cortex (IC) that is just dorsal and caudal to this region (visceral cortex). Lesions in anterior GC were without effect. Here, neurotoxic bilateral lesions were placed in the anterior half of this critical damage zone, at the confluence of the posterior GC and the anterior visceral cortex (termed IC2 ), the posterior half of this critical damage zone that contains just VC (termed IC3 ), or both of these subregions (IC2 + IC3 ). Then, pre‐ and postsurgically acquired CTAs (to 0.1 M NaCl and 0.1 M sucrose, respectively) were assessed postsurgically in 15‐minute one‐bottle and 96‐hour two‐bottle tests. Li‐injected rats with histologically confirmed bilateral lesions in IC2 exhibited the most severe CTA deficits, whereas those with bilateral lesions in IC3 were relatively normal, exhibiting transient disruptions in the one‐bottle sessions. Groupwise lesion maps showed that CTA‐impaired rats had more extensive damage to IC2 than did unimpaired rats. Some individual differences in CTA expression among rats with similar lesion profiles were observed, suggesting idiosyncrasies in the topographic representation of information in the IC. Nevertheless, this study implicates IC2 as the critical zone of the IC for normal CTA expression. J. Comp. Neurol. 524:54–73, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Bilateral ibotenic acid lesions were targeted to the area of insular cortex (IC) where gustatory cortex and visceral cortex (VC) are conjoined (in IC2 ) and/or the area of VC just posterior to that (in IC3 ). Rats impaired on postsurgical conditioned taste aversion (CTA) expression tests had significantly more damage in IC2 than unimpaired rats. Damage to IC3 was not associated with CTA deficits.